Challenges of Smallholder Farming in Ethiopia and Opportunities by Adopting Climate-Smart Agriculture - Zerssa, Gebeyanesh; Feyssa, Debela; Kim, Dong-Gill; Eichler-Löbermann, Bettina (Agriculture (Basel), 2021)
Agriculture is the backbone of the Ethiopian economy, and the agricultural sector is dominated by smallholder farming systems. The farming systems are facing constraints such as small land size, lack of resources, and increasing degradation of soil quality that hamper sustainable crop production and food security. The effects of climate change (e.g., frequent occurrence of extreme weather events) exacerbate these problems. Applying appropriate technologies like climate-smart agriculture (CSA) can help to resolve the constraints of smallholder farming systems. This paper provides a comprehensive overview regarding opportunities and challenges of traditional and newly developed CSA practices in Ethiopia, such as integrated soil fertility management, water harvesting, and agroforestry. These practices are commonly related to drought resilience, stability of crop yields, carbon sequestration, greenhouse gas mitigation, and higher household income. However, the adoption of the practices by smallholder farmers is often limited, mainly due to shortage of cropland, land tenure issues, lack of adequate knowledge about CSA, slow return on investments, and insufficient policy and implementation schemes. It is suggested that additional measures be developed and made available to help CSA practices become more prevalent in smallholder farming systems. The measures should include the utilization of degraded and marginal lands, improvement of the soil organic matter management, provision of capacity-building opportunities and financial support, as well as the development of specific policies for smallholder farming.